The Influence of Training, Work Motivation, and Leadership Style Toward the Performance of State Civil Apparatus at The Marine Transportation Education and Training Center - Wahyudi, Ilham; Mulyadi, Mohammad (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2025)
When it comes to work results in terms of quality, punctuality, work initiative, and communication, the ASN performance phenomena at the Marine Transportation Education and Training Center is subpar. The study is to partially and simultaneously examine the impact of leadership style, work motivation, and training on the performance of State Civil Apparatus at the Marine Transportation Education and Training Center. This study employs an explanatory methodology and a quantitative research design. Just 47 ASN completed the google form out of the 52 ASN that were part of the ASN study at the Marine Transportation Education and Training Center. In order to make all populations into samples, the sampling technique used saturated samples. Several linear regression analysis approaches were employed in the data analysis process. The study's conclusions.